PENGEMBANGAN MAKANAN TRADISIONAL BALI PADA PASAR MALAM DI PASAR SINDU, SANUR, BALI - Nelsye Lumanaw (Jurnal Ilmiah Hospitality Management, 2018)
Sindu night market becomes a favorite place for tourists, who stay in Sanur area to enjoy Indonesian traditional food. Many traditional foods available at this market, such as nasi campur Banyuwangi, sate-gule kambing Madura, soto, bakso. Sate-gule kambing has become the most popular food at this market, followed by nasi campur Banyuwangi. Traditional Balinese food is also available at this market. It has strong taste and unique processing, but still not able to compete with others. This research aims to develope Balinese traditional food by using qualitative method that divided into theory and the application. The theoretical part is traditional food, traditional market, culinary tourism, environmental analysis, strength-weakness- opportunityâ€“threat (SWOT) and resource based view (RBV). The application part is to analyse internal-external factors. SWOT matrix indicates four development strategics for the Balinese traditional food, such as comfort of the market, unique foods, documentary and cooperation with other tourism industry. Â Keywords: traditional food, traditional market, culinary tourism, development strategy, resources-based view.